Does Inability to Allocate Attention Contribute to Balance Constraints during Gait in Older Adults? - Siu, Ka-Chun (2008)
BACKGROUND: Recent research has explored dual-task deficits during locomotion in older adults, yet the mechanisms underlying these deficits are poorly understood. In the current study, we examined one possible factor contributing to these deficits, the inability to flexibly allocate attention between two tasks. METHODS: Twelve healthy young adults and 12 healthy elderly adults performed obstacle avoidance while walking and an auditory Stroop task either alone or simultaneously. RESULTS: Using an attentional allocation index (AAI) to compare performance of healthy young and older adults and to measure the flexibility of allocation of attention, results showed a tendency in older adults toward a decreased ability to flexibly allocate their attention between the two tasks, with small AAI values. The decreased ability to allocate attention in older adults was found to be more prominent in the auditory Stroop task performance than in the obstacle avoidance task. CONCLUSION: This study suggests that an important factor contributing to decreased dual-task performance in older adults when simultaneously performing a postural and secondary cognitive task is a reduced ability to flexibly allocate attention between the two tasks, with the general ability to switch attention flexibly being predictive of the ability to adhere to a prioritized focus.